Relationship between Self-Efficacy and Anxiety Level in Pre Operative Cataract Patient at Balung Hospital Jember - Siswoyo Siswoyo; Kushariyadi Kushariyadi; Deka Isnatu Raka Joni (NurseLine Journal, 2020)
Cataract causes lowering visibility and becomes the main risk factor of blindness that can be healed by performing surgery. The surgery may cause anxiety which is affected by self efficacy. Thus, the self efficacy boost the human’s confidence in making decision, reducing stress, as well as lowering the depression risk. The objective of this research is to analyze the correlation between self efficacy and the level of anxiety to the pre-cataract operation patients at Balug Regional Hospital. This research comprises 2 variables there are self-efficacy (independent variables) and the level of anxiety (dependent variable) that is observed using descriptive analytical method by using purposive sampling. The data collection method used in this research is perfomed by using Pre Operative Self Efficacy Scale (PSES) to assess self efficacy and The Amsterdam Preoperative Anxiety and Information Scale (APAIS) to determine the level of anxiety. The analysis of the correlation between self efficacy and the level of anxiety is conducted by using The Spearman Rank Correlation (p=0,05). The result of this research reveals the median score of the self efficacy is 146,00 with the average of 131,48. The percentage of self efficacy reveals as many as 53 respondents (84,1%) show good self efficacy as opposed to 10 respondents (15,9%) who show poor self efficacy. The percentage of the repondents’ level of anxiety reveals as many as 39 respondents (61,9%) show mild level of anxiety. The result of this research also reveals the correlation between self efficacy and the level of anxiety of the pre-cataract operation patients (p = 0,001 r = -0,691) with negative direction. This means that the higher self efficacy, the lower level of anxiety is. Conclusion: Self efficacy plays important roles in controlling anxiety. Any individuals with high confidence may control what happens, thus allowing low level of anxiety to appear, respectively.